Mechanisms of Creativity Differences Between Art and Non-art Majors: A Voxel-Based Morphometry Study - Xurui, Tan; Yaxu, Yu; Qiangqiang, Li; Yu, Mao; Bin, Zhou; Xueming, Bao (Frontiers in Psychology, 2018)
Creativity is considered the ability to generate new ideas or behaviors, an ability that has diverse expressions in different human groups, such as painters and nonpainters. Art major students require more creative activities than nonart students do. In this study, we plan to explore the figural creativity abilities of art major students and whether these students benefit from their professional training relative to nonart majors. Therefore, in this study, we use voxel-based morphometry (VBM) to identify different behavioral and brain mechanisms between art major students and nonart major students by using the figural Torrance Test of Creative Thinking. Our results showed that the TTCT-figural (TTCT-F) scores of art majors were higher than those of nonart majors. Subsequently, the interaction analysis revealed that the TTCT-figural scores of art majors and nonmajors exhibited significant correlations with the gray matter volumes of the left anterior cingulate cortex (ACC) and the left medial frontal gyrus (MFG). While the sample slope analysis showed that art majors, compared with nonart majors, exhibited a marginal significantly positive association with the left ACC and MFG, nonart majors exhibited a significantly negative association with the left ACC and MFG. Overall, our study revealed that people who major in artistic work are more likely to possess enhanced figural creative skills relative to nonartistic people. These results indicated that professional artistic programs or training will increase creativity skills via reorganized intercortical connections.